Pitfalls, Myths, and Errors in Pulse Oximetry: Understanding False Readings in Severe Hypoxemia - Avramovska, Maja; Nikleski, Zorica; Siklovska, Vesna; Todorovska, Liljana; Taleva, Biljana; Stefanovska, Svetlana; Avramovski, Petar (ECRONICON open acesss, 2025)
Pulse oximetry is a widely used, non-invasive method for monitoring oxygen saturation (SpO2) in clinical and specialized settings, including maritime and high-altitude medicine. However, several pitfalls and misconceptions can lead to false readings, particularly in cases of severe hypoxemia. This mini-review explores the limitations of pulse oximetry, the role of perfusion index (PI) in assessing peripheral circulation, and common sources of measurement errors, such as low perfusion states, motion artifacts, and skin pigmentation. The clinical interpretation of SpO2 levels is discussed, emphasizing the need for caution when readings fall below 65%, where peripheral cyanosis is evident, rendering further saturation assessment redundant. Additionally, a nomogram illustrating the relationship between SpO2, partial pressure of oxygen (PaO2), pH, and PaCO2 is presented, aiding in the understanding of respiratory acidosis and alkalosis. The review also highlights the importance of SpO2 monitoring in critical conditions, including cytokine storm syndromes, and discusses the integration of Bluetooth-enabled pulse oximeters for real-time data transmission. Understanding the limitations and proper interpretation of SpO2 readings is crucial for avoiding misdiagnosis and ensuring accurate clinical decision-making.
Keywords: Oxygen Saturation (SpO2); Pulse Oximetry; Hypoxemia; Perfusion Index (PI)